EVALUATION OF NEUTRON SCATTERING IN FUSION REACTOR DIAGNOSTICS AND TILE MATERIAL - Lengar, Igor (Journal of Energy Technology, 2024)
The neutron diagnostics systems in fusion reactors, mainly used to measure plasma parameters, are exposed to direct – plasma – neutrons and an indirect component of scattered neutrons. Detectors are usually experimentally calibrated with known neutron sources in order to account for both components. In tokamaks, minor changes in the torus structure are frequently performed, which can influence the scattered neutron contribution to the detector response and possibly deteriorate its calibration. The influence of scattered neutrons can be important in particular for components close to the detector positions. The positions from which the neutrons are scattered prior to their detection in detector systems and the influence of the first wall material on the neutron backscattering are investigated in the paper. The study is performed for a typical inͲvessel diagnostic, located in the upper part of the torus. The tile material influence is performed for the most frequently used materials, namely carbon, beryllium and tungsten. The neutron transport code MCNP was used. The estimation was performed for neutron fluxes in a typical fusion reactor spectrum.